PENGARUH FAKTOR KEPERILAKUAN ORGANISASI TERHADAP KEGUNAAN SISTEM AKUNTANSI KEUANGAN DAERAH (Studi Kasus Pada Instansi Pemerintahan Kabupaten Gresik) - Shofiyah Shofiyah; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to obtain empirical evidence regarding the effect of training, clarity of objectives and superiors' support for the usefulness of the regional financial accounting system. This research was conducted at the Gresik Regency Government Office. Based on the purposive sampling method, a sample of 97 respondents was obtained. The data was collected by using a questionnaire, then testing the hypothesis using multiple regression analysis. Simultaneously training, clarity of objectives and superiors' support affect the usefulness of the regional financial accounting system. Partially the training variable, clarity of objectives and superiors' support have a positive influence on the usefulness of the regional financial accounting system. Keywords: training, clarity of purpose, superiors support and the utility of the regional financial accounting system